(3bUjOI fhfjI aj hUa hJOHjQ GdMLQ GdecQes - (3eMeO Hf Cejd Hf YHO Gddg Hf Cejd GdJejej , CHh YHO Gddg , (B170 (3g`s
(3ChdgG (B:s
(3CKGQ GdHjf hLOc hGdMfjfG YTjI hOY GdeJMedjfG s
(3BNQgG (B:s
(3hEf GdfaS bO SdcJg WhYG hYQVG HYO ZSd GdZGSdjfG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B36 - (3U(B37s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B88 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs